Two new species of plant parasitic nematodes Hirschmanniella bananae n.sp. (Nematoda: Pratylenchidae) and Scutellonema tanlamense n.sp. (Nematoda: Hoplolaimidae) associated with banana in Vienam - Chau, Nguyen Ngoc (Academia Journal of Biology, 2017)
During investigation on the plant parasitic nematodes on bananas in North and Central provinces of Vietnam carried out in 1995 two new species were found, Hirschmanniella bananae n.sp. and Scutellonema tanlamese n.sp. Hirschmanniella bananae n.sp. is characterized by having 6 annuli in lip region, areolation of entire lateral field and presence of a mid-terminal mucro at the tail end. The new species is close to H. shamini Ahmad, 1972 but differs from H. shamini by longer body length in females (1450-1750 µm vs 1190-1360 mm), longer stylet longer (18-20.5 mm vs 16-19 mm) and longer spicule longer (28-29.5 mm vs 22-25 mm). Scutellonema tanlamese n.sp. is characterized by lip region with three annuli and numerous longitudinal ridges (18) in basal annulus and structure of lateral field at the tail region with inner lines extending to tail terminus. The new species is closest to S. brachyurus type B (African populations) described by Van Den Berg et al. in 2013 but can be distinguished by body length shorter (643-708 µm vs 777-820 µm), stylet length shorter ((24.5-26.5 µm vs 28-29.5 mm, and also by structure of lateral field with two inner lines going throught at tail region and vulval edge distinct with epiptygma appearing double and folded into vagina.   Citation: Nguyen Ngoc Chau, 2017. Two new species of plant parasitic nematodes Hirschmanniella bananae n.sp. (Nematoda: Pratylenchidae) and Scutellonema tanlamense n.sp. (Nematoda: Hoplolaimidae) associated with banana in Vienam. Tap chi Sinh hoc, 39(3): 253-263. DOI: 10.15625/0866-7160/v39n3.10665. *Corresponding author: nguyengochau.iebr@gmail.com Received 19 August 2017, accepted 12 September 2017